Escala temporal da turbulência para escoamento noturno acima da copa de uma floresta tropical úmida na Amazônia - Campos, Jose Galucio (2008)
The LBA (Large Scale Biosphere-Atmosphere in Amazônia) project has been using the eddy covariance technique since 1998 to continuously monitor the surface fluxes of energy, water vapor and carbon over Amazônia. The results obtained up to now indicate high level of uncertainties, especially regarding the role of the Amazonian ecosystem to the global carbon budget. Besides the problems related with the Eddy measure system (systematic error and nighttime stable conditions), there is an important factor associated with the averaging time scale or time window used by the scientific community to determine the surface fluxes. This work focuses on the determination of the nocturnal turbulence time scale for long term surface fluxes (carbon, energy and water) over the Amazon rainforest. We used the multi-resolution decomposition technique to project the signal into several time scales and determine when the spectral and co-spectral gap occurred. This technique permitted evaluating and separating the real contribution from turbulent and mesoscale fluxes to the total nocturnal surface fluxes. Our results indicate that the nighttime turbulence time scale is near 100 seconds. It suggests that the time averaging commonly used to calculate nocturnal surface fluxes (30 minutes), needs to be revised. Besides, our results show that, when the mesoscale flux contributions were included, the total nocturnal surface flux was generally underestimated.